Cocoanut [sic] Palms, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2009)
A picture of coconut trees growing close to the waters edge. Postcard numbered 6455.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago